Evaluation of Two Mini-implant Lengths in the Infrazygomatic Crest Region: A Randomized Clinical Trial - Alsaeedi, Abbas F.; Alrubayee, Mehdi Abdul-hadi; Sivamurthy, Gautham (European Journal of Dentistry, 2024)
Objective  Temporary anchorage devices (TADs) have revolutionized fixed orthodontic appliance treatment through anchorage controlling in the clinic and play an essential role in resolving many complex cases. Due to the limited space, there is a risk of injury to the roots while using interradicular microimplants. Therefore, the infrazygomatic crest (IZC) area can be an alternative mini-implant insertion site in the maxillary arch. The aim of the study was to evaluate the primary stability, pain perception, sinus penetration, late stability, and failure rate with two mini-implant lengths in the IZC area.Materials and Methods Forty-eight mini-implants (Tusk Dental Co., Ltd., Canada) with two different lengths (length/diameter: 12/2 and 14/2 mm) were grouped by length (24 per group) and inserted bilaterally into the IZC area of 24 patients. The data were statistically analyzed, considering a significance level of p < 0.05.Results Sinus penetration prevalence did not differ significantly between 12-mm (54.2%) and 14-mm (62.5%) mini-implants (p > 0.05). Primary stability was significantly higher with the 14-mm mini-implants (p < 0.05). The failure rate did not differ significantly between the 12-mm (20.8%) and 14-mm (16.7%) mini-implants (p > 0.05).Conclusion While the failure rate was similar between 12- and 14-mm mini-implants, the 14-mm mini-implants were more likely to damage adjacent structures. Therefore, shorter mini-implants should be preferred over longer mini-implants for most cases requiring IZC TADs.Trial Registration ID ClinicalTrials.gov identifier: NCT06293872.
Keywords: miniscrews; infrazygomatic crest area; TADs; orthodontics; mini-implant